Faktor-Faktor Kunci dalam Meningkatkan Kualitas Laporan Keuangan Pemerintah Daerah - Library, Ni Putu Ani Lutfya; Utama, I Made Karya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
One sign of strong and accountable government is the government's management's superb financial reporting. This study sought to analyze the influence of accounting expertise, HR skills, control systems, and leadership styles in the Badung Regency Government's OPD's financial report quality. The number of participants was decided by recruiting 104 finance professionals from each outpatient department using a selective selection strategy. The data was assessed and processed using SPSS 27's multiple linear regression analysis. Accounting expertise, human resource competence, an efficient internal control system, and leadership style were shown to have a beneficial influence on the quality of financial reports. Both stewardship theory and empirical investigations into the trustworthiness of financial reporting find theoretical support in this work. Practically speaking, this research gives the Badung Regency Government and other regional governments data they may use to make better financial reporting.